Sociodemographic, health-related and lifestyle correlates of physical activity in adults with current asthma. (2nd January 2017) - Good, Joshua; Jagroop, David; Dogra, Shilpa
ABSTRACT: Objective : Regular physical activity is associated with better asthma control; however, little is known of the determinants of physical activity in a population of adults with asthma. Thus, the purpose of this study was to identify important sociodemographic, health and lifestyle correlates of physical activity among adults with asthma. Methods : Data from adults with asthma aged 18–44 years ( n = 2740) from the Canadian Community Health Survey (CCHS), 2011–2012 annual component were used for analysis. The main outcome was Daily Energy Expenditure (DEE). This variable was based on frequency and duration of leisure activities in the past 3 months. Self-reported sociodemographic (age, sex, total household income, highest education level, and ethnicity), health-related (body mass index (BMI), self-perceived health, mood disorder, anxiety disorder, and asthma symptoms/attacks, past year) and lifestyle (type of smoker, sedentary time, fruit and vegetable consumption) variables were assessed as correlates for DEE. Data were analysed using linear regressions. Results : In the final model, sociodemographic correlates accounted for 4.2% of the variation in DEE. Adding health correlates increased the R 2 to 12.1%. Finally, adding lifestyle correlates increased the R 2 to 17.6%. Conclusions : In adults with current asthma, the main correlates of physical activity are age, total household income, BMI, self-perceived health, anxiety disorder, sedentary time, and fruit and vegetable consumption. These data are important for informing education and exercise interventions for adults with asthma. Future research is needed to determine asthma-specific correlates of physical activity.